2017
DOI: 10.1002/ecs2.1934
|View full text |Cite
|
Sign up to set email alerts
|

Range loss of a threatened grouse species is related to the relative abundance of a mesopredator

Abstract: Citation: K€ ammerle, J.-L., J. Coppes, S. Ciuti, R. Suchant, and I. Storch. 2017. Range loss of a threatened grouse species is related to the relative abundance of a mesopredator. Ecosphere 8(9):e01934. 10. 1002/ecs2.1934 Abstract. Mammalian generalist mesopredators can reach high densities in forest-farmland mosaic landscapes in the absence of top-down control. The abundance of generalist mesopredators is a potentially limiting factor for prey populations, especially ground breeding birds such as grouse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 86 publications
0
36
0
1
Order By: Relevance
“…Home‐range sizes obtained through VHF telemetry in parts of the study area (Kaphegyi, ) suggest low to intermediate red fox density (below five individuals km −2 ; Šálek, Drahníková, & Tkadlec, ). Management of red fox populations is incentivized in the study area, because red foxes are considered important predators of capercaillie ( Tetrao urogallus ), a locally threatened grouse species (Kämmerle et al, ). Grouse are ground nesting birds and thus vulnerable to predation of eggs and chicks as well as adult birds (Storch, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Home‐range sizes obtained through VHF telemetry in parts of the study area (Kaphegyi, ) suggest low to intermediate red fox density (below five individuals km −2 ; Šálek, Drahníková, & Tkadlec, ). Management of red fox populations is incentivized in the study area, because red foxes are considered important predators of capercaillie ( Tetrao urogallus ), a locally threatened grouse species (Kämmerle et al, ). Grouse are ground nesting birds and thus vulnerable to predation of eggs and chicks as well as adult birds (Storch, ).…”
Section: Methodsmentioning
confidence: 99%
“…The area is characterized by a land use mosaic dominated by mixed montane forests (approximately two-thirds forest cover, Braunisch & Suchant, 2007), fragmented by settlements, single farms, and agricultural land cover types (primarily livestock pastures; Figure 1). For more information on the study area, see Kämmerle, Coppes, Ciuti, Suchant, and Storch (2017) and Kämmerle, Corlatti, Harms, and Storch (2018). Red foxes occur in all parts of the study area and their relative abundance varies in relation to landscape configuration (Güthlin et al, 2013).…”
Section: Study Area and Speciesmentioning
confidence: 99%
“…The Black Forest capercaillie population is isolated from other populations in central Europe (Segelbacher et al., ) and highly fragmented (Braunisch, Segelbacher, & Hirzel, ; Coppes et al., ). Population size and distribution have been continuously decreasing over the last 30 years (Coppes et al., ), with the cause considered to be multifactorial, including habitat deterioration (Suchant & Braunisch, ), habitat fragmentation (Braunisch et al., ), predator abundance (Kämmerle et al., ), disturbance through human recreation (Coppes et al., ) as well as climate change (Braunisch et al., ; Huntley, Green, Collingham, & Willis, ).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we collected faecal samples across the entire geographical range of an endangered central European capercaillie population. We chose capercaillie as an ideal study model because FCM are calibrated (Thiel et al., ), they occur in various landscapes (Klaus et al., ) and they respond to various stressors such as predation (Kämmerle, Coppes, Ciuti, Suchant, & Storch, ), climate change (Braunisch et al., ), habitat degradation (Suchant & Braunisch, ) and human disturbance (Coppes et al., ) while being threatened throughout their central European range (Storch, ). By combining FCM measurements in three consecutive winters with genetic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2016, Lyly et al 2016, Kämmerle et al 2017, while one study found such a relationship only for one of several grouse species (Tornberg et al 2013). In Sweden, Lindström et al (1994) monitored red foxes and three grouse species at several spatial scales during a sarcoptic mange outbreak and concluded that predation by foxes is limiting grouse abundance.…”
Section: Qualitative Review Predation and Population Limitationmentioning
confidence: 99%